Mobilność edukacyjna jako punkt zwrotny w biografii jednostki - Łuczak, Marta (Studia Edukacyjne, 2020)
The increasing number of migrations is the main quality of modern society. Formerly, migration was a single action of leaving one’s country of origin, aimed at settling in a new place. Nowadays, migration should be described as a mobility that is a repeated change of the country of residence and a temporary stay in a new place. The status of mobility has a huge influence on modifying personal identity through the experience of life in different cultures. The article indicates the reasons for educational mobility and its consequences for personal biography. The change of self-definitions influences the further personal process of life.